Two-temperature thermodynamic and transport properties of SF6–Cu plasmas. (24th September 2015) - Wu, Yi; Chen, Zhexin; yang, Fei; Cressault, Yann; Murphy, Anthony B; Guo, Anxiang; Liu, Zirui; Rong, Mingzhe; Sun, Hao
Abstract: SF6 and Cu are widely adopted in electrical equipment as a dielectric medium and for conductive components, respectively. SF6 –Cu plasmas are frequently formed, particularly in high-voltage circuit breaker arcs and fault current arcs, due to erosion of the Cu components. In this paper, calculated values of the thermodynamic and transport properties of plasmas in SF6 –Cu mixtures are presented for both thermal equilibrium and non-equilibrium conditions. The composition is determined by the two-temperature Saha equation and Guldberg–Waage equation in the form derived by van de Sanden. The composition and the thermodynamic properties are evaluated through a classical statistical mechanics approach. For the transport coefficients, the simplified Chapman–Enskog method developed by Devoto, which decouples the electrons and heavy species, has been applied using the most recent collision integrals. The thermodynamic and transport properties are calculated for different electron temperatures (300–40 000 K), ratios of electron to heavy-species temperature (1–10), pressures (0.1–10 atm) and copper molar proportions (0–50%). It is found that deviations from thermal equilibrium strongly affect the thermodynamic and transport properties of the SF6 –Cu plasmas. Further, the presence of copper has different effects on some of the properties for plasmas in and out of thermal equilibrium. The main reason for these changes is that dissociation reactions are delayed for non-thermal equilibrium plasmas, which in turn influences the ionization reactions that occur.